ANALISIS PENAGIHAN PIUTANG PADA PERUM PERUMNAS PROYEK BANDUNG II - Firman Prayoga; Ramadhan Pancasilawan (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to analyze the accounts receivable collection process carried out at Perum Perumnas Bandung II Project using indicators of collection methods through letters, telephone calls, personal visits, and legal action. This research uses a descriptive qualitative method. The results showed that the Perum Perumnas Bandung II Project in collecting receivables was still not optimal. Limited human resources and a limited budget for conducting accounts receivable collection activities are obstacles to optimally implementing the accounts receivable collection process. This study provides recommendations for allocating a special budget to collecting accounts receivable and adding specific human resources to manage and carry out accounts receivable collection activities. The results of this study are expected to be a reference in collecting bad debts that are more effective and optimal.